Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1109/tac.2006.884993
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dynamic Simulation Allocation in Ordinal Optimization

Abstract: Safety stocks are set to minimize inventory costs-the cost function in problem (15)-using as input the buyer's demand model, the service level agreement-the constraint in problem (15)-and (a model of) the production capacities B i n . We will explore how demand parameters can be adjusted according to both supplier and buyer cost structures so that any generated savings can be shared among them.We assume that the buyer's demand is an m-state Markov-modulated process (MMP), with transition probability matrix PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 12 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…Both KG and coordinate optimization methods work well when the immediate benefits realized by their decisions are in harmony with longterm progress. While the KG approach does not work well in all information collection problems, and should be applied with care (see Chen et al (2006) for a perfect information R&S problem for which a myopic policy required modification to perform well), it has been successfully applied to at least two other R&S problems ; ), and promises to produce a class of principled yet flexible algorithms for information collection.…”
Section: Introductionmentioning
confidence: 99%
“…Both KG and coordinate optimization methods work well when the immediate benefits realized by their decisions are in harmony with longterm progress. While the KG approach does not work well in all information collection problems, and should be applied with care (see Chen et al (2006) for a perfect information R&S problem for which a myopic policy required modification to perform well), it has been successfully applied to at least two other R&S problems ; ), and promises to produce a class of principled yet flexible algorithms for information collection.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2006), He et al (2007), Fu et al (2007 and Chen et al (2008) also address the question of computing budget allocation under various scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…However, the sequential approach is an effective way to estimate the unknown variance, and several studies have demonstrated significant efficiency gains in using sequential allocation versus one-time or twostage allocation (cf. Inoue et al 1999, Chen et al 2006.…”
Section: Ocba-m Allocation Proceduresmentioning
confidence: 99%